El principio de gratuidad judicial como derecho fundamental, para las publicaciones de los extractos judiciales - Zapatier Arellano, Carmen Ivonne (2015)
This research leads to the importance of legal knowledge of constitutional guarantees enshrined in our Constitution; rule is violated by not observed its application in processes, as regards judicial gratuity. To do this, you start with the development of the problem and its respective justification, based on a social reality that undermines what enshrined in our Constitution, which actually living parts of judicial process evidence. Arises as main objective to establish a standard to ensure and promote the constitutional principle of judicial gratuity and that effective, impartial and expeditious protection is given, which must be applied by the three constitutional principles that are the speed, immediacy and helplessness. The right of defense of every person must be a party to proceedings can not be deprived of it, since the Constitution provides, therefore they must be applied several safeguards to prevent their violation. With all the items of evidence collected in the investigation, such as teaching, law, comparative law and fieldwork, we conclude with the proposal, within which they can substantiate and justify its formulation, the same applying for reform to Code of Civil Procedure in Chapter regards citations by press to ensure compliance with the constitutional principle of judicial gratuity.